Incentivizing the use of a second language in the hospitality industry through contests involving all hotel staff: Challenges and benefits (2022)
This work is based on my first semester of internship as it was the one that allowed me to have my first formal experience in the workplace. Selina Cartagena tested all my knowledge, skills and values. During my work as a receptionist, I understood how the world of hospitality works from different points of view and perceptions while the functions are fulfilled, from which I learned that if you do things with love and passion, everything will be better. I was fortunate to meet wonderful people and work with an incredible team, along with the guidance of the excellent supervisor I had. I learned how interpersonal relationships should be within the field of hospitality tourism.